Arterial stiffness in patients with non-alcoholic fatty liver disease is related to fibrosis stage and epicardial adipose tissue thickness - SÜNBÜL, MURAT; ERGELEN, RABİA; YILMAZ, YUSUF (ELSEVIER IRELAND LTD, 2014)
Objective: Non-alcoholic fatty liver disease (NAFLD) is associated with atherosclerosis and reduced vascular compliance. The purpose of this study was to examine the relationships between arterial stiffness measures, the histological severity of NAFLD, and epicardial fat thickness (EFT). Methods: A total of 100 patients with biopsy-proven NAFLD and 50 age-and sex-matched controls were enrolled. The histological severity was assessed in all NAFLD patients. Measurements of arterial stiffness [pulse-wave velocity (PWV) and augmentation index (AIx)] were carried out using a Mobil-O-Graph arteriograph system. EFT was assessed by means of echocardiography. Results: Compared with controls, NAFLD patients had significantly higher PWV and AIx values. Stepwise linear regression analysis demonstrated that the liver fibrosis score and EFT were independent predictors of both PWV and AIx values in NAFLD patients. Conclusions: Patients with NAFLD have an increased arterial stiffness, which reflects both the severity of liver fibrosis and increased EFT values. (C) 2014 Elsevier Ireland Ltd. All rights reserved.
Keywords: Nonalcoholic fatty liver disease; Arterial stiffness; Pulse wave velocity; Augmentation index; Epicardial fat thickness; PULSE-WAVE VELOCITY; METABOLIC SYNDROME; NAFLD; RISK